Standardisasi Nafkah Istri: Studi Perbandingan Mazhab Maliki dan Mazhab Syafi’i - Karimuddin Karimuddin; Syahrizal Abbas; A. Hamid Sarong; Afrizal Afrizal (Media Syari'ah, 2021)
The standard of living for the wife that is obliged to be provided by the husband is not clearly defined in the Koran and the hadiths, thus requiring the scholars to perform ijtihad in determining the size of the wife's income. The results of the ulama's ijtihad regarding the size of the wife's income will differ along with the different methods of ijtihad and the argument used, so that it becomes ambiguous (obscure) for the community to understand the actual size of the living according to the opinion of certain schools of thought. Based on the description of the problem, it is necessary to have an in-depth study of the standardization of the wife's income, which the author limits according to the Maliki and Shafi'i school. In this study the authors used a qualitative research method with a normative approach. The results of the research of the Maliki school of wife's income were not determined by a certain size, but the wife's obligation to support her was according to the husband's income level and the level of the wife's needs, so the Maliki school did not see the wife's obligation to support the husband's rich or poor. While the Shafi'i school determines the level of the wife's income with two classifications, food and clothing are determined according to the husband's class of income, while the residence or house is determined according to the wife's family stratum and the wife's eligibility to live in. Based on the results of this study, it can be concluded that the standardization of the wife's income is determined according to the ijtihad of different scholars according to the ijtihad method used.Standar nafkah istri yang wajib diberikan suami tidak ditentukan secara jelas dalam Alquran dan hadis, sehingga mengharuskan para ulama untuk berijtihad dalam menentukan ukuran nafkah istri tersebut. Hasil ijtihad para ulama tentang ukuran nafkah istri akan berbeda seiring dengan berbedanya metode ijtihad dan dalil yang digunakan, sehingga menjadi ambigu (kekaburan) bagi masyarakat untuk memahami ukuran nafkah yang sebenarnya menurut pendapat mazhab tertentu. Berdasarkan deskripsi permasalahan tersebut perlu ada sebuah kajian yang mendalam tentang standardisasi nafkah istri yang penulis batasi menurut mazhab Maliki dan Syafi’i. Dalam kajian ini penulis menggunakan metode penelitian kualitatif dengan pendekatan perbandingan hukum (comparative approach). Hasil penelitian ditemukan bahwa dalam mazhab Maliki nafkah istri tidak ditentukan ukuran tertentu namun kewajiban nafkah istri tersebut menurut kadar penghasilan suami dan kadar kebutuhan istri, jadi mazhab Maliki tidak melihat kewajiban nafkah istri tersebut kepada kaya atau miskinnya suami. Sementara mazhab Syafi‘i menentukan kadar nafkah istri dengan dua klasifikasi, untuk makanan dan pakaian ditentukan menurut kelas perhasilan suami, sementara untuk tempat tinggal atau rumah ditentukan sesuai dengan strata keluarga istri dan kelayakan istri untuk menetap di dalamnya. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa standardisasi nafkah istri ditentukan menurut ijtihad para ulama yang berbeda sesuai dengan metode ijtihad yang digunakan.